The Role of Environmental Management Concept in the Supply Chain - Urbaniak, Maciej (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The purpose of this article is to define the role of environmental management in the implementation of the concept of a Green Sustainable Supply Chain. Widespread interest in the implementation of this concept determines the environmental activities which are undertaken by companies. For this reason, more and more organizations are interested in the introduction of an environmental management system (based on the requirements of the ISO 14000 family of standards). The involvement of companies in the implementation of the concept of sustainable development is also reflected in the propagation of this idea among business partners in the supply chain. Undertaking activities mitigating the negative impact on the environment is considered by many organizations an important criterion in the initial and periodic assessment of suppliers. Many companies, while working on developing of a strong and positive brand image among their customers, use environmental labels when promoting their products. In recent years, more and more companies implement the material flow cost accounting concept which takes into consideration the relationships in the supply chain.